Cultural Tourism in Mauritius From Rhetoric to Reality (Global Journal of Human-Social Science, 2018)
This conceptual paper builds on the assertion that though there is a dire need to revisit the traditional tourist attractions of Mauritius in order to increase earnings offset seasonality of beach tourism and boost up competitiveness and attractiveness of the destination not much headway has been made to diversify the country s tourism sector through the development of cultural tourism It is proven that this type of tourism not only attracts high-spending visitors to a host country but also helps consolidate its arts and culture sector Albeit the fact that there has been a rich rhetoric as regards the necessity for a convergence of arts and culture and tourism in Mauritius very few concrete actions have been undertaken so far Based on a combination of theories of marketing and psychology the author under takes a review of the relevant literature enumerates the main rhetoric pertaining to cultural tourism in Mauritius as stated in the official documents of the country and through critical thinking and reflective analysis puts forth a conceptual model and some action-oriented proposals on how cultural tourism could be realised concretely in this country together with their justifications The author also brushes over the main obstacles that could be impeding this kind of tourism
Keywords: culture; cultural tourism; cultural tourist; tourist motivation; rhetoric; reality